Sosialisasi Penggunaan Google Bisnis pada UMKM untuk Meningkatkan Pemasaran dan Penjualan Produk Muria Jaya di Desa Mulyasari Kota Banjar - Darisman, Dede; Pauziah, Alya Lutfhi; Hardiyanti, Fitri (Khidmat, 2022)
The proliferation of information technology and the internet has created fresh avenues for Micro, Small and Medium Enterprises (MSMEs) to enhance the marketing and sales of their products. A viable tool for this purpose is Google Business, a platform specifically developed to facilitate the expansion of local enterprises. Muria Jaya UMKM is a company specializing in the production of tofu and tempeh. The objective of this service initiative is to enhance the market penetration of Muria Jaya micro, small, and medium enterprises (MSMEs) through the process of digitalizing their marketing efforts. The proposed solution in this activity involves the implementation of digital marketing through the utilization of the Google Business platform. UMKM Muria Jaya can enhance their visibility to potential customers by utilizing this platform's capabilities, including business listings, customer reviews, and geographical information, which facilitate easy discovery of their items via the Google search engine. The approach employed in this activity involves the formation of an activity team, doing visits, performing analysis, implementing activities, and conducting evaluations. The outcome of the service efforts is the Google Business platform, which serves as an online marketing and sales tool.